Providing resource information to users of a national computing center. (5th March 2014) - Hanlon, Matthew; Smith, Warren; Mock, Stephen; Wilkins‐Diehr, Nancy; Majumdar, Amit
SUMMARY The Texas Advanced Computing Center provides a variety of high‐end resources to state, national, and international computational scientists and engineers. Many users obtain information about these resources via the Texas Advanced Computing Center user interfaces, which are supported by an information gathering and distribution infrastructure. After a number of years of use, we needed to improve our user interfaces by both redesigning the web interface and adding mobile interfaces. To support this, we also needed to update our information infrastructure. This paper presents our new design, describes how it improves over the previous approach, and shows that this design meets our current and expected future needs. Copyright © 2014 John Wiley & Sons, Ltd.